The acceptance of using e-book among primary school teachers / Nor Aini Hassanuddin, Zalinawati Abdullah and Norudin Mansor - Hassanuddin, Nor Aini; Abdullah, Zalinawati; Mansor, Norudin (2013)
Background of Research - E-book project was introduced to pursue the government's call in information and communication technology (ICT). The usage of e-book was still new in Malaysia and Terengganu was the first state to use the e-book. Objective - The purpose of this research is to find out the teachers’ acceptance level towards the usage of e-book in the Dungun District. E-book is now becoming a hot topic especially in academic world in Terengganu. Design/Methodology/Approach- The sampling method used in this study is stratified random sampling by schools. Self-administered questionnaires will be distributed randomly among respondents in primary schools at 2 selected DUNs in Dungun. Analysis/Findings - The study uses SPSS (Scientific Package for Social Sciences). Overall, this specified into Frequencies Distribution, Descriptive Analysis, Reliability Analysis, Correlation Coefficient (Pearson’s) and Regression Analysis. The study found that there was a significant difference between the teachers’ demographic profiles with the acceptance of e-book in DUNs Sura and Rantau Abang. There is also a significant relationship between the acceptances and independent variables (IT Knowledgeability, Students’ Attitudes, Students’ Learning Independent, and Ergonomics).